Evolution of the electron-to-ion temperature ratio of cold plasma in the lobes - Li, Kun; Chen, Junhan; Chai, Lihui; Kronberg, Elena; Doepke, Nicolas (Frontiers in Astronomy and Space Sciences, 2025)
Cold plasma of ionospheric origin, with energies less than a few tens of electronvolts, dominates the plasma population in the magnetosphere and plays a crucial role in magnetospheric dynamics. Although the velocity distribution of cold plasma in the magnetotail is measured, little is known about the changes in its temperatures because of the difficulty in directly measuring the cold plasma. In this study, we examine the electric field measurements in the plasma wake, which is created by charged spacecraft interacting with the cold plasma flow, to infer the changes in the electron-to-ion temperature ratio of the cold plasma. We present observations from the Cluster mission during the years 2001–2010 and the distributions of the observed electric potential decrease in the plasma wake. The results confirm the correlation between the wake potential and the plasma flow speed and indicate that the electron-to-ion temperature ratio of the cold plasma decreases with increasing geocentric distance, suggesting that electrons are heated differently from ions as the cold plasma is transported into the tail.